2021
DOI: 10.1039/d1fd00024a
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic exploration of xenon/krypton separation based on a high-throughput screening

Abstract: Nanoporous framework materials are a promising class of materials for energy-efficient technology of xenon/krypton separation by physisorption. Many studies on Xe/Kr separation by adsorption have focused on the determination of...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 93 publications
5
38
0
Order By: Relevance
“…While one can typically expect selectivity to drop at higher pressure due to weaker host–guest interactions, it is also possible to observe a cooperative effect between sorbates enhancing the selectivity. 59 Thus, such comparisons should preferably be made after obtaining selectivities at the same pressure conditions.…”
Section: Resultsmentioning
confidence: 99%
“…While one can typically expect selectivity to drop at higher pressure due to weaker host–guest interactions, it is also possible to observe a cooperative effect between sorbates enhancing the selectivity. 59 Thus, such comparisons should preferably be made after obtaining selectivities at the same pressure conditions.…”
Section: Resultsmentioning
confidence: 99%
“…[160][161][162] Such computational screening methods have recently witnessed a rapid expansion due to several factors such as (1) the growth of the open public databases, (2) the advances in methods for hypothetical structural construction, and (3) the development of artificial intelligence techniques. [163][164][165] In fact, machine learning techniques have now shown great promise in MOF science because it is not feasible to experimentally single out top-performing structures from the vast and ever-growing MOF library, which now exceeds >70,000 MOF structures. In this Faraday discussion, high-throughput computational screening of MOF in applying xenon/krypton separation, 165 methane storage, 166 and biogas purification 167 were discussed.…”
Section: Theory and Modelingmentioning
confidence: 99%
“…[163][164][165] In fact, machine learning techniques have now shown great promise in MOF science because it is not feasible to experimentally single out top-performing structures from the vast and ever-growing MOF library, which now exceeds >70,000 MOF structures. In this Faraday discussion, high-throughput computational screening of MOF in applying xenon/krypton separation, 165 methane storage, 166 and biogas purification 167 were discussed. They demonstrated that their methods provide the best candidates and a better comprehension of the structure-property relationships in the target application.…”
Section: Theory and Modelingmentioning
confidence: 99%
“…Computational studies can be invaluable in directing experimental efforts efficiently toward promising MOFs. On a particularly large scale, the diverse chemical space occupied by MOFs makes them a prime target for high-throughput computational screenings. ,, Large data sets of structures can be studied using relatively cheap computational methods, as in Glover and Besley’s search of nearly 7,000 MOFs for biogas upgrading properties. Promising MOFs identified by computational screenings are often the subject of detailed investigations using more intensive computational methods, which remain significantly faster than experimental studies.…”
Section: Introductionmentioning
confidence: 99%